PTS TOOL SAFETY ANALYSIS ON VERTICAL GEOTHERMAL PRODUCTION WELL USING FLUID FLOW MODELLING - FUAD SATRIO AJIE (NIM : 22611004);, R.
Well characteristics such as pressure, temperature, fluid flow, and productivity index are some of the basic information that needs to be obtained in order to maximize the utilization also monitoring of the reservoir. PTS survey is commonly used to obtain these information. The vertical movement of PTS tool along the wellbore is controlled by constant velocity wire while centralizer and additional weight are attached to the tool to maintain the position. The safety of the PTS tool is very important. Some of the failure cases occurred on the liner of the well-bore configuration due to the upward fluid-force was greater than the additional weight. A numerical study has been developed to understand this phenomenon. A fluid-flow model was built to simulate the behavior of the tool (with the additional weight that was calculated from the fluid properties of the well-bore casing of FSA-1 production well) in the liner using the ANSYS-FLUENT fluid-flow modeller. The PTS tool model is defined within a cylindrical well-bore liner with the boundary condition based on data obtained from the former PTS survey. Through this fluidflow simulation, this study has found the safe additional weight that should be attached to eliminate the possibilities of tool failures.